Vertical galvanic corrosion of pipeline steel in simulated marine thermocline. (1st December 2020) - Deng, Peichang; Li, Ziyun; Li, Xiaogang; Hu, Jiezhen; Wang, Gui
Abstract: The dramatic changes of temperatures, pH values, dissolved oxygen contents, and nutrients typically occur in marine thermocline, which are the key factors giving rise to the corrosion of metals. Exploitation of offshore oil and gas has made marine metals gradually moving into deep sea and increased their penetration into the marine thermocline. This study investigates the corrosion of X70 pipeline steel in marine thermocline by simulating seawater thermocline identical to the formation mechanism of marine thermocline. Specifically, the corrosion of X70 pipeline steel was analyzed by means of wire beam electrode (WBE) technique, linear polarization (LP), corrosion morphology, and weight loss measurement. Results indicated that the steel's galvanic currents increased with experimental time, and the galvanic corrosion got worse vertically from the top to the bottom of the marine thermocline simulator. Corrosion on the upper part of the long steel was due to the temperature and dissolved oxygen in the upper thermocline regime, and on the lower part primarily due to the galvanic corrosion in the lower regime. The corrosion products of X70 pipeline steel were high-valence iron compounds for the high content of dissolved oxygen in upper thermocline layer, but low-valence iron compounds in the anoxic middle and lower layers. The rusts were composed of two layers, namely, a fluffy outer layer with poor adhesion and a thin inner layer with strong adhesion. The inner layer rust of the X70 pipeline was covering a smaller steel area in the lower part of the thermocline for the anodic activation of galvanic corrosion. Highlights: Galvanic corrosion occurs after intrusion of the X70 pipeline steel into the simulated marine thermocline. The galvanic currents increased with experimental time. The galvanic corrosion gradually worsened in the vertical from the top to the bottom of the marine thermocline simulator. At about the 10th day, the anode and cathode reversed location. Galvanic corrosion was the primary cause of corrosion of the part of the long X70 pipeline steel in the lower part of the thermocline. In contrast, temperature and dissolved oxygen were the corrosion elements on the upper part of thermocline.